Financial Inclusion and Economic Justice: The Role of Digital Finance in Empowering Indonesia’s Poor (Indonesian Economic Justice Review, 2025)
This paper investigates the role of digital finance in promoting economic justice in Indonesia, with a particular focus on how digital financial services can empower the country's poor and marginalized populations. As Indonesia’s financial sector increasingly embraces digital technologies, the unbanked and underbanked populations—often located in rural areas or from lower-income backgrounds—are gaining access to financial services such as mobile banking, microloans, and digital payment systems. This study critically assesses the potential of digital finance to reduce financial exclusion and enhance economic opportunities for marginalized groups. By reviewing the impact of government initiatives like the National Financial Inclusion Strategy (NFIS) and the development of digital payment systems such as Gojek’s GoPay and OVO, the paper explores how digital platforms are bridging the gap between traditional financial institutions and underserved communities. The paper also highlights the challenges associated with digital financial inclusion, including digital literacy, cybersecurity risks, and regulatory hurdles. It finds that while digital finance holds significant promise for improving financial access, it requires targeted policy interventions to ensure equitable participation and to address the digital divide. The paper concludes with recommendations for enhancing financial inclusion through improved infrastructure, better digital literacy programs, and strengthened regulatory frameworks to protect vulnerable users.